Vadba hoje s sistemom Lokomat pri bolnikih po možganski kapi - Stanonik, Irena (Rehabilitacija (Ljubljana), 2013)
Abstract Re-establishing gait is an important part of rehabilitation for patients after cerebral stroke (CS). In the recent years, additional therapeutic procedures such as electromechanical devices for gait training have been increasingly used in rehabilitation beside the conventional neurological physiotherapy approaches. Those devices cannot replace conventional neurological physiotherapy; however, they offer additional possibilities of gait training and decrease non-ergonomic physical stress of therapists. The present article is a survey of research findings on gait training with the Lokomat electromechanical device in patients after CS in different phases of recovery after stroke, its advantages, shortcomings and the different possibilities for training that it offers.
Keywords: acute cerebral stroke; chronic cerebral stroke; electromechanical devices; elektromehanske naprave; gait training; hoja; možganska kap; neurological physiotherapy; nevrofizioterapija; rehabilitacija; Rehabilitation; Stroke; vadba hoje; vocational rehabilitation